Towards Equity for Students and Teachers of Colour: Insights into Pedagogies, Emotions and Initiatives in Science Education - Martin Ako; Oluwatoyin Imisoluwa Jegede; Shamnaz Arifin Mim (Canadian Journal for New Scholars in Education)
In this paper, we reviewed recent literature on equity pedagogies and initiatives for students of colour as well as the role of teachers’ emotions in science education, especially for teachers of colour within K-12 contexts. Our review was guided by two questions: a) how do conceptualization of equity inform the design and implementation of equity-oriented initiatives to promote academic success among students of colour and b) how can emotions be leveraged to understand identity construction of science teachers of colour to further inform equity initiatives? Our findings reveal that, while equity initiatives have gained prominence in education, there are varied meanings and understandings of equity that inform how equity pedagogies and initiatives are developed and enacted. The study has important implications for educators, researchers and policymakers. It provides a comprehensive overview of the current debates about equity pedagogies, initiatives and the role of emotions in fostering the identity of science teachers of colour.